2000
DOI: 10.1002/1096-9861(20000724)423:2<261::aid-cne6>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of leptin-activated neurons in the rat brain

Abstract: Leptin has profound effects on food intake, body weight, and neuroendocrine status. The lack of leptin results in hormonal and metabolic alterations and a dramatic increase in body weight. Leptin acts in the brain, especially in the hypothalamus; however, the central nervous system sites that respond to leptin have not been examined comprehensively. In this study, we explored systematically the distribution of leptin-activated neurons throughout the rat brain. Furthermore, we investigated the chemical identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
1
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(194 citation statements)
references
References 135 publications
9
179
1
5
Order By: Relevance
“…Integration of leptin signals with other systems mediating a variety of homeostatic mechanisms, such as reproduction (Mantzoros, 2000;Schneider et al, 2000) may take place at the level of the arcuate nucleus by virtue of common populations of peptidergic neurons with divergent connections. For example, injections of leptin activate both NPY and POMC neurons in the arcuate nucleus, which project to regions such as the paraventricular and dorsomedial nuclei and appear to convey leptin based signals (Elias et al, 2000), but arcuate neurons also project to GnRH cells in the preoptic region (Chen et al, 1989;Li et al, 1999). Thus, different physiological functions may be coordinated by interactions between neurons located in the arcuate nucleus through common activation by leptin, or possibly through communication organized by local circuits in the arcuate nucleus.…”
Section: Figurementioning
confidence: 99%
“…Integration of leptin signals with other systems mediating a variety of homeostatic mechanisms, such as reproduction (Mantzoros, 2000;Schneider et al, 2000) may take place at the level of the arcuate nucleus by virtue of common populations of peptidergic neurons with divergent connections. For example, injections of leptin activate both NPY and POMC neurons in the arcuate nucleus, which project to regions such as the paraventricular and dorsomedial nuclei and appear to convey leptin based signals (Elias et al, 2000), but arcuate neurons also project to GnRH cells in the preoptic region (Chen et al, 1989;Li et al, 1999). Thus, different physiological functions may be coordinated by interactions between neurons located in the arcuate nucleus through common activation by leptin, or possibly through communication organized by local circuits in the arcuate nucleus.…”
Section: Figurementioning
confidence: 99%
“…ObRb neurons are certainly expressed in the VMN and peripheral leptin administration induces c-Fos and pSTAT3 in VMN neurons [70,71]. Additionally, ewes with a lesioned ARC show a similar extent of c-Fos activation in response to iv leptin treatment as control ewes [65], arguing for direct action of leptin on populations of VMN neurons.…”
Section: The Ventromedial Nucleusmentioning
confidence: 99%
“…Interestingly, although peripheral leptin treatment in mice induce increased pSTAT3-immunoreactivity in the NTS [104] and induce c-Fos in several nuclei of the brainstem including the NTS [70], Elias and colleagues observed that very few leptin induced c-Fos positive neurons in the brainstem actually express ObRb mRNA. The NTS is the only brain region in addition to the ARC that contain POMC neurons, however there is controversy over their characteristics.…”
Section: The Brainstem Circuits and Satietymentioning
confidence: 99%
“…PMv neurons project to the POA and other nearby regions, where elements of the reproductive axis reside, and the PMv regulates reproductive behavior in males and coordinates GnRH release and ovulation in response to seasonal and other inputs in females [89][90][91][92][93][94][95][96][97][98][99]. PMv LRb neurons represent a major population of LRb-expressing/ leptin-responsive neurons in the brain [88].…”
Section: The Neural Basis Of Leptin Actionmentioning
confidence: 99%